(untitled) (World Bulletin of Physical Education and Sports Science, 2026)
This article examines effective methods for improving ball passing and receiving skills in volleyball players within the context of sports education at pedagogical universities. The study is grounded in the idea that accurate passing and stable reception are fundamental technical components determining both individual performance and team coordination during training and competition. The paper analyzes methodological approaches aimed at developing these skills through structured repetition, differentiated drills, situational exercises, and integrated physical preparation. Special attention is given to the relationship between technical accuracy, movement coordination, reaction speed, spatial orientation, and decision-making under game conditions. The research emphasizes that the improvement of passing and receiving cannot be achieved solely through mechanical repetition, but requires a pedagogically organized system that combines technique correction, tactical awareness, and psychological stability. Training tasks designed for various levels of preparedness are discussed, including pair exercises, group combinations, target-oriented passing drills, and game-based reception practice. The article also highlights the importance of feedback, error analysis, and gradual complication of exercises in the formation of durable motor skills. It is argued that the use of modern instructional methods in volleyball education contributes not only to technical mastery but also to learners’ confidence, discipline, and cooperative competence. The findings suggest that systematic and scientifically grounded training methods significantly enhance the quality of passing and receiving, thereby increasing the overall effectiveness of volleyball instruction in higher pedagogical education.